1999
DOI: 10.1590/s0104-42301999000100008
|View full text |Cite
|
Sign up to set email alerts
|

A laparoscopia no diagnóstico das doenças intra-abdominais. Análise de 168 casos

Abstract: RESUMO -radiológicas não-invasivas de imagem (ultrassonografia, tomografia etc.) e o método não foi muito difundido entre os gastrenterologistas e cirurgiões gerais, sendo mais utilizado pelos ginecologistas. Llanio et al 7 foram pioneiros em divulgar o método como eficaz em avaliar urgên-cias abdominais. Foi pouco valorizado durante alguns anos e na década de 90 novamente passou a ser muito empregado, desta vez no diagnóstico do abdômem agudo, traumatismos e ferimentos abdominais 8 . A partir de 1986, após Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
2
0
9
Order By: Relevance
“…The cause and symptoms of the present study were similar as observed in studies of Baria, Fayez et al, Schrenk et al [11][12][13] In the study, diagnostic laparoscopy was done in 63 patient and the etiology was identified in around 93.65% (59) cases and these findings are comparable to previously done aforementioned studies of Andreollo et al and Salky et al 14,15 According to the studies of Andreollo the etiology identified by laproscopy was around 86.3% cases of 168 patients and in the study of Salky the percentage of identified cases was 76% of 265 patients.…”
Section: Discussionsupporting
confidence: 91%
“…The cause and symptoms of the present study were similar as observed in studies of Baria, Fayez et al, Schrenk et al [11][12][13] In the study, diagnostic laparoscopy was done in 63 patient and the etiology was identified in around 93.65% (59) cases and these findings are comparable to previously done aforementioned studies of Andreollo et al and Salky et al 14,15 According to the studies of Andreollo the etiology identified by laproscopy was around 86.3% cases of 168 patients and in the study of Salky the percentage of identified cases was 76% of 265 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrasound-guided kidney biopsies are considered the standard method for humans and animals [ 2 , 8 ], but laparoscopy can be recommended in specific cases, as seen for obese or pediatric human patients, cases of high blood pressure or hemostasis disorders, and for small-sized dogs in veterinary medicine [ 1 , 8 , 9 ]. Various researchers highlight the safety of the laparoscopic procedure [ 3 , 4 , 10 – 12 ] supported by studies where it was shown to be better than the ultrasound-guided biopsy [ 7 ]. However, the inadequate performance of this technique and the lack of skills of the operator enhance the risks for complication due to the kidney biopsy procedure, among other factors [ 1 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esse estudo apresentou como complicações tardias póslaparoscopias os implantes metastáticos nos locais de inserção de trocartes e agulha de biopsia, hérnias nos locais de incisão e infecção intra-abdominal. 10 Um outro estudo da Faculdade de Medicina de Universidade de São Paulo expõe as evidências até o momento, tanto favoráveis como desfavoráveis ao tratamento radical do câncer colorretal por acesso videolaparoscópico. Nesse estudo, os autores relatam evidências da ocorrência de recidivas tumorais em sítios de punção de trocartes após operações curativas para câncer colorretal e realizadas por acesso videolaparoscópico, totalizando pelo menos 30 casos.…”
Section: Resultsunclassified